Microfinance Investment Funds Leveraging Private Capital for Economic Growth and Poverty Reduction - Matthäus-Maier, Ingrid; Pischke, J. D. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The surge in new investment funds - nearly 60 funds at last count - is an exciting sign that microfinance is attracting mainstream financial markets. Foreign investors bridge a crucial gap for MFIs and greenfield banks not yet able to attract deposits, debt or equity from local sources. Recognizing the ultimate goal of building those local financial markets that serve the poor, some foreign investors and funds are facilitating local intermediation with incentives like guarantees for local banks to lend to MFIs in local currency. Such contributions to local market building, combined with strengthening governance, increasing transparency and rigor make the new funds potentially very positive forces in microfinance. Elisabeth Littlefield, Director and CEO, CGAP Microfinance investment funds organised as mutual funds and structured finance products are bringing the vast resources of capital markets to the world of microfinance, which is about empowering poor people through provision of user-friendly financial services. These funds and structured products are superb means of producing a combination of financial and social returns. Individual and institutional investors are increasingly interested in the characteristics of microfinance loan portfolios. Progress in defining microfinance investments as an asset class is underway. In order to attract more commercial investors to microfinance, new financial instruments will have to be developed that satisfy commercial risk-return criteria while achieving the social benefits of microfinance activities. Jean-Philippe de Schrevel, Founder and Director, BlueOrchard Finance S.A.